Turning one into five: Integrative taxonomy uncovers complex evolution of cryptic species in the harvester ant Messor “structor” - Steiner, Florian M.; Csősz, Sándor; Markó, Bálint; Gamisch, Alexander; Rinnhofer, Lukas; Folterbauer, Clemens; Hammerle, Sarina; Stauffer, Christian; Arthofer, Wolfgang; Schlick-Steiner, Birgit C. (Soil Organisms, 2018)

Ant genus Strongylognathus (Hymenoptera, Formicidae) in Bulgaria: a preliminary review - Lapeva-Gjonova, A.; Radchenko, A. G. (Biodiversity Data Journal, 2021)

First Records of Two Strumigenys Ant Species (Hymenoptera, Formicidae) from Bulgaria - Lapeva-Gjonova, Albena; Ljubomirov, Toshko (Sociobiology, 2020)
The Strumigenys ant species (Hymenoptera: Formicidae) are poorly studied in Bulgaria due to their small size and cryptic lifestyles. To date, only one species, S. baudueri (Emery, 1875), has been reported from a collecting site in the East Rhodopi Mountains (South Bulgaria). Herein we provide the fi rst records of another two species in Bulgaria: S. argiola (Emery, 1869) (Northeast Bulgaria) and S. tenuipilis Emery, 1915 (South Pirin Mountain). Scanning electron microscope micrographs of both species are also provided.
Keywords: Attini; Balkan Peninsula; Myrmicinae; new records

Socially parasitic ants of Greece. - Buschinger A.; Douwes P. (Biologia Gallo-Hellenica, 1993)

The slave-making ant genus Chalepoxenus (Hymenoptera, Formicidae). I. Review of literature, range, slave species. - Buschinger A.; Ehrhardt W.; Fischer K.; Ofer J. (Zoologische Jahrbücher. Abteilung für Systematik, Ökologie und Geographie der Tiere, 1988)

Three species of Aphaenogaster Mayr, 1853 (Hymenoptera: Formicidae) new to the Bulgarian fauna - Borowiec, Lech; Lapeva-Gjonova, Albena; Salata, Sebastian (Acta Zoologica Bulgarica, 2019)
Three new species of the family Formicidae (Hymenoptera) are recorded for the first time from Bul- garia: Aphaenogaster festae Emery, 1915 (East Rhodopes), Aphaenogaster radchenkoi Kiran & Tezcan, 2008 (South Pirin and Struma Valley) and Aphaenogaster subterraneoides Emery, 1881 (North Black Sea coast, Eastern Rhodopes and Sakar Mt.). The present record of A. radchenkoi is the first for Europe and the occurrence of A. festae establishes its northern range border in Bulgaria. A list of 23 species recorded in Bulgaria after publishing its catalogue of ant species in 2010 is presented.
Keywords: Aphaenogaster; Bulgaria; Formicidae; new records

Inconvenient hyperdiversity – the traditional concept of “Pheidole pallidula” includes four cryptic species (Hymenoptera: Formicidae) - Seifert, Bernhard (Soil orranisms, 2016)

Myrmica vandeli Bondroit (Hymenoptera: Formicidae) - a new ant species for Bulgaria - Anna M. Stankiewicz; Vera Antonova (Acta Zoologica Bulgarica, 2005)

Towards DNA-aided biogeography: An example from Tetramorium ants (Hymenoptera, Formicidae) - Florian M. Steiner; Birgit C. Schlick-Steiner; Matthias Sanetra; Toshko Ljubomirov; Vera Antonova; Erhard Christian; Christian Stauffer (Ann. Zool. Fennici, 2005)

First record of Myrmica rugulososcabrinodis Karawajew (Hymenoptera, Formicidae) for Bulgaria - Radchenko, Alexander G; Antonova, Vera (Myrmecologische Nachrichten, 2004)

First record of the slave-maker ant Harpagoxenus sublaevis (Nylander, 1849) from Bulgaria (Hymenoptera: Formicidae) - Antonova, Vera (Myrmecological News, 2009)
Harpagoxenus sublaevis (Nylander, 1849) was found among ants taken in pitfall traps set in the Alibotoush Reserve, Slavjanka Mountain in southwestern Bulgaria. This species is new to the Bulgarian myrmecofauna that recently numbered about 130 species.
Keywords: Bulgaria; Formicidae; Harpagoxenus sublaevis; social parasite

First records of three ant species (Hymenoptera: Formicidae) from Bulgaria - Lapeva-Gjonova, Albena (Myrmecological News, 2011)
Three Mediterranean ant species – Camponotus aegaeus EMERY, 1915, Camponotus gestroi EMERY, 1878 and Crematogaster auberti EMERY, 1869 – were found on Bulgarian territory for the first time. The report of Camponotus aegaeus for Bulgaria is the first for continental Europe as well. The total number of known ant species for Bulgaria increases to more than 160.
Keywords: ants; Bulgaria; Camponotus; Crematogaster; Formicidae

Unusual Ant Hosts of the Socially Parasitic Ant Anergates atratulus (Schenck, 1852) (Hymenoptera, Formicidae) - Lapeva-Gjonova, Albena; Kiran, Kadri; Aksoy, Volkan (Psyche, 2012)
The extreme inquiline ant Anergates atratulus (Schenck, 1852) (Hymenoptera, Formicidae) was collected in ant nests of Tetramorium moravicum Kratochvil, 1941 in Bulgaria and of T. chefketi Forel, 1911 in Bulgaria and Turkey. The reported ant hosts belong to the Tetramorium chefketi species complex in contrast with the typical hosts from Tetramorium caespitum/impurum complex. This finding confirms the assumption that a broader range of host species for the socially parasitic species A. atratulus may be expected. Present data on the new host species expand knowledge about biology of this rare ant species, included in the IUCN Red List of threatened species.